2021
DOI: 10.3389/fcosc.2021.727819
|View full text |Cite
|
Sign up to set email alerts
|

Barrier to Gene Flow of Grey Mangrove Avicennia marina Populations in the Malay Peninsula as Revealed From Nuclear Microsatellites and Chloroplast Haplotypes

Abstract: Contemporary mangrove forest areas took shape historically and their genetic connectivity depends on sea-faring propagules, subsequent settlement, and persistence in suitable environments. Mangrove species world-wide may experience genetic breaks caused by major land barriers or opposing ocean currents influencing their population genetic structure. For Malay Peninsula, several aquatic species showed strong genetic differentiation between East and West coast regions due to the Sunda shelf flooding since the La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 102 publications
1
3
0
Order By: Relevance
“…Our results showed that the genetic diversity of R. mucronata was moderate (I = 0.573, Ho = 0.619, He = 0.391, Table 2 ). The same result has been found in previous mangrove studies, such as Avicennia marina worldwide [ 77 ], A. marina in the Malay Peninsula [ 60 ], and Kandelia obovata in China [ 78 ]. In addition, low genetic diversity of Rhizophora species was detected in several studies carried out in Japan, Brazil, Mexico, Southeast Asia, and the Indo-West Pacific region [ 14 , 31 , 32 , 61 , 70 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results showed that the genetic diversity of R. mucronata was moderate (I = 0.573, Ho = 0.619, He = 0.391, Table 2 ). The same result has been found in previous mangrove studies, such as Avicennia marina worldwide [ 77 ], A. marina in the Malay Peninsula [ 60 ], and Kandelia obovata in China [ 78 ]. In addition, low genetic diversity of Rhizophora species was detected in several studies carried out in Japan, Brazil, Mexico, Southeast Asia, and the Indo-West Pacific region [ 14 , 31 , 32 , 61 , 70 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, in a genetic study of R. apiculata using SNP markers, it was reported that the Gulf of Thailand population separated from the Andaman population [ 21 ]. Moreover, several studies have reported high differentiation between mangrove populations on both sides of the Malay Peninsula, including Ceriops tagal [ 54 , 55 ], Bruguiera gymnorrhiza [ 56 , 57 ], Excoecaria agallocha [ 58 ], Sonneratia alba [ 57 , 59 ], Avicennia marina [ 60 ], and Avicennia alba [ 57 ]. Meanwhile, our results showed that the Malay Peninsula has a minimal effect on the R. mucronata species.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accord to the present study findings. Different studies have reported both long-range connection of mangrove trees in relation to ocean currents and direction, especially along same coastlines, and also the occurrence of a stepping-stone model of migration between estuaries [ 36 , 37 ]. The present study aligns with several studies throughout the world, which shows that.…”
Section: Discussionmentioning
confidence: 99%
“…While many terrestrial forest restoration programs incorporate genetic information to strengthen the resistance and resilience of forest ecosystems to environmental changes, restoration programs for marine ecosystems-including mangrove forests-have rarely 10.3389/ffgc.2022.784322 done so, partly due to a lack of empirical data on genetic diversity and structure of the studied ecosystem, or to the complexity and costs of genetic/genomic approaches (Coleman et al, 2020). To the best of our knowledge, no mangrove (re-)establishment program have thus far considered genetic information in their planning phase (only in the monitoring phase; e.g., Granado et al, 2018), despite the increase in knowledge about genetic variation in mangrove ecosystems gained over the last two decades (e.g., Dodd et al, 2002;Triest, 2008;Wee et al, 2015;Hodel et al, 2018;Azman et al, 2020;Mantiquilla et al, 2021;Triest et al, 2021).…”
Section: The Role Of Genetic Diversity In (Re-)establishmentmentioning
confidence: 99%